The Rounded Corner Surmounted by a Spire: Introduction and Evolution of an Haussmannian Model in Bilbao (1885-1906) (BSAA arte, 2019)
The model for rounded corners surmounted by a spire, emerging in Paris in the mid-nineteenth century, greatly influenced many other parts of the world. This article focuses on the establishment and evolution of these types of structures, specifically in the case of tenement houses built in Bilbao between 1885 and 1906, the period of validity of the municipal building ordinances that came into force at the first mentioned year. This article also addresses the conflicts that were generated owing to the regulations set, the interests in real estate, and their implications on the urban layout. Many of these structures, especially the finishings, were suppressed or replaced by new ones during the second third of the twentieth century, but became protected at the onset of the eighties.
Keywords: architecture; Bilbao; municipal building ordinances; 19th century; 20th century